Gendered impacts of COVID-19: Insights from 7 countries in Sub-Saharan Africa and South Asia - Alvi, Muzna; Gupta, Shweta; Barooah, Prapti; Ringler, Claudia; Bryan, Elizabeth; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2022)
It is widely recognized that periods of crisis affect men and women differently, mediated by their access to resources and information, as well as social and institutional structures that may systematically disadvantage women from being able to access relief, institutional support, and rehabilitation. To capture the gendered impacts of the COVID-19 pandemic and lockdowns, we conducted phone surveys in seven countries spread across Asia and Africa. The study was designed as a longitudinal panel study with five rounds of data collection in Ghana, Nepal, Nigeria, and Senegal, and three rounds of data collection in Kenya, Niger, and Uganda. Both men and women were administered the same survey, with some modifications made across countries to adapt to local contexts. This report gives an overview of our findings covering several topics including income loss, coping strategies, labor and time use, food and water insecurity and child education outcomes. We find widespread reports of income loss, which declined over time, but increased again as countries experienced a resurgence in COVID-19 cases and fatality. We find that households first depleted savings when faced with income loss and over time, use of savings reduced while other measures began to be adopted. Women reported greater food and water insecurity compared to men, including worrying about insufficient food and eating less than usual. This is particularly worrying since a large proportion of women also did not have adequately diverse diets. Moderate to severe water insecurity was reported in many of the countries, and as with food insecurity, women were more likely to report issues with accessing water for drinking and other household activities. In some countries, additional modules were added to capture country specific issues of policy relevance, such agriculture extension, mental health, and child marriage. The results make it clear that proactive investments will be needed, including social safety nets, favorable credit policies, nutrition and water investments, to ensure that the crisis does not further widen the gender gap in resources and achievements in rural areas of low- and middle-income countries.